Uterotonic Neuromedin U Receptor 2 and Its Ligands Are Upregulated by Inflammation in Mice and Humans, and Elicit Preterm Birth. Issue 3 (1st September 2016) - Nadeau-Vallée, Mathieu; Boudreault, Amarilys; Leimert, Kelycia; Hou, Xin; Obari, Dima; Madaan, Ankush; Rouget, Raphaël; Zhu, Tang; Belarbi, Lydia; Brien, Marie-Ève; Beaudry-Richard, Alexandra; Olson, David M.; et al.
Abstract: Uterine labor requires the conversion of a quiescent (propregnancy) uterus into an activated (prolabor) uterus, with increased sensitivity to endogenous uterotonic molecules. This activation is induced by stressors, particularly inflammation in term and preterm labor. Neuromedin U (NmU) is a neuropeptide known for its uterocontractile effects in rodents. The objective of the study was to assess the expression and function of neuromedin U receptor 2 (NmU-R2) and its ligands NmU and the more potent neuromedin S (NmS) in gestational tissues, and the possible implication of inflammatory stressors in triggering this system. Our data show that NmU and NmS are uterotonic ex vivo in murine tissue, and they dose-dependently trigger labor by acting specifically via NmU-R2. Expression of NmU-R2, NmU, and NmS is detected in murine and human gestational tissues by immunoblot, and the expression of NmS in placenta and of NmU-R2 in uterus increases considerably with gestation age and labor, which is associated with amplified NmU-induced uterocontractile response in mice. NmU- and NmS-induced contraction is associated with increased NmU-R2-coupled Ca ++ transients, and Akt and Erk activation in murine primary myometrial smooth muscle cells (mSMCs), which are potentiated with gestational age. NmU-R2 is upregulated in vitro in mSMCs and in vivo in uterus in response to proinflammatory interleukin 1beta (IL1beta), which is associated with increased NmU-induced uterocontractile response and Ca ++ transients in murine and human mSMCs; additionally, placental NmS is markedly upregulated in vivo in response to IL1beta. In human placenta at term, immunohistological analysis revealed NmS expression primarily in cytotrophoblasts; furthermore, stimulation with lipopolysaccharide (LPS; Gram-negative endotoxin) markedly upregulates NmS expression in primary human cytotrophoblasts isolated from term placentas. Correspondingly, decidua of women with clinical signs of infection who delivered preterm display significantly higher expression of NmS compared with those without infection. Importantly, in vivo knockdown of NmU-R2 prevents LPS-triggered preterm birth in mice and the associated neonatal mortality. Altogether, our data suggest a critical role for NmU-R2 and its ligands NmU and NmS in preterm labor triggered by infection. We hereby identify NmU-R2 as a relevant target for preterm birth.